Report of the Committee on Finance (House doc. (North Carolina. General Assembly. House of Commons) ;, 1850)
1840 Report of the Committee on Finance regarding the North Carolina House of Commons resolution to provide information regarding four different expenditures of money. This included the clerks' hire to sell Cherokee land, compensation for various other hires, and salaries for agents selling stock in a railroad.